Pure niobia as catalyst for the oxidation of organic contaminants: Mechanism study via ESI-MS and theoretical calculations - Oliveira, Luiz C. A. (2007)
In this work, synthetic and natural niobium oxide (niobia), were used to promote the oxidation of methylene blue dye. The samples were characterized by XRD, XPS and FTIR measurements. The presence of reactive species on the surface of the samples strongly increases the oxidation rate of the methylene blue dye. The reaction mechanism was studied by ESI-MS analyses. Moreover, kinetic data and XPS spectroscopy suggest that the oxidation of the organic dye involves oxidizing species mainly generated after previous treatment with H2O2. The results also showed that the oxidation takes place by a homolytic mechanism via radical intermediates.